2020
DOI: 10.1108/amhid-10-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic mixed-methods review of changing “case-complexity” of referrals to an intensive support service

Abstract: Purpose “Case-complexity” is a widely used but under-explored concept across health and social care. A region’s Intensive Support Teams (ISTs) had been reporting an increase in “case-complexity”, but had not tested this hypothesis against data. This study aims to investigate this question through a pragmatic mixed-methods approach as part of a wider service evaluation. Design/methodology/approach Health of the Nation Outcome Scales for People with Learning Disabilities (HoNOS-LD) scores were used (n = 1,766)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The HoNOS-LD is one of several scales recommended for use in English intellectual disability services (e.g. NHS England 2017) and has been used in several clinical studies, as an outcome measure for hospital wards (Hillier et al 2010), for therapy evaluations (Skelly et al 2018) and as a means of managing caseload complexity (Clifford and Kemp 2020). Published studies have either used the total score for the HoNOS-LD (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The HoNOS-LD is one of several scales recommended for use in English intellectual disability services (e.g. NHS England 2017) and has been used in several clinical studies, as an outcome measure for hospital wards (Hillier et al 2010), for therapy evaluations (Skelly et al 2018) and as a means of managing caseload complexity (Clifford and Kemp 2020). Published studies have either used the total score for the HoNOS-LD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies have either used the total score for the HoNOS-LD (e.g. Skelly et al 2018;Clifford and Kemp 2020) or studies have used clusters of scores based on clinical opinion or face validity as suggested by Harris et al 2018(e.g. Hillier et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This included extracting key information and codes on discharge outcomes. Health of the Nation Outcome Scales (HoNOS) were collected for all accepted referrals as an additional indicator of case-complexity at point of referral (Clifford and Kemp, 2020). Thematic analysis (Braun and Clarke, 2006) was used as the qualitative methodology for examining and extracting key information from referral documents and casenotes, using elements of Robinson's (2022) tabular approach for investigating brief texts.…”
Section: Design and Methodologymentioning
confidence: 99%